High school students’ preconceptions about the concept of climate change considered from the perspective of visual representation - Yani, Sindi; Sari, Lasmita; Fitria Amalia, Irma; Nurahman, Arip (Research in Physics Education, 2024)
Preconceptions are an essential foundation for students, serving as a basis for more effective learning. In the context of climate change concepts, many students harbor misconceptions. One method to uncover students’ preconceptions is through the use of visual representations. Visual representations can elucidate students’ understanding of abstract and complex concepts. This study aims to examine and analyze the extent of high school students’ comprehension of climate change. The research employs a descriptive qualitative approach, with a population and sample comprising 63 tenth-grade science students from a high school in Indonesia. Data collection techniques included observation and interviews, with semi-structured interviews being utilized in this study. The results reveal that students have varied understandings of the concept of climate change, with many exhibiting misconceptions. The study identifies three categories of climate change concepts: (1) correct concepts of climate change, representing 37%; (2) climate change concepts based on objects, as depicted in the visualizations provided by the respondents; and (3) incorrect concepts of climate change, representing 63%. Based on empirical evidence, the students’ preconceptions of climate change are predominantly at the macroscopic level.